HOW ANTIOXIDANT AND ANTIOXIDANT ENZYME FUNCTIONS DO SUPPRESSED IN THE BRAIN TISSUES OF DEVELOPING CHICK EMBRYO UNDER THE INFLUENCE OF ACRYLAMIDE? - M. VENKATASWAMY,; M. MEENABAI,; K. VENKATASUBBAIAH,; K. J. RAO,; RAJU, K. THYAGA (The Bioscan, 2013)
Acrylamide a known neurotoxin is produced due to amino acid metabolism in the body. This molecule adversely affects the central nervous system by the operation of the free radicals and oxidative stress. These oxygenated molecules potential has been studied in brain tissue of day (11) (d11) developing chick embryo exposed to acrylamide at different concentrations (0.1, 0.2, 0.3, 0.4, 0.5 and 0.6mg) and times of intervals (24, 48 and 72h). Upon exposure of chick embryo to acrylamide the level of lipid peroxidation (LPO) product, malondialdehyde (MDA) increased and the contents of antioxidants i.e., reduced glutathione (GSH) and ascorbic acid (Vit-C) was decreased, significantly, in brain. The activities of antioxidant enzymes, glutathione-S-transferases (GSTs) and superoxide dismutase (SOD) have been increased up to 0.4mg and declined from 0.5 to 0.6mg due to dose and time dependant of acrylamide treatment and the activities of glutathione peroxidase (GPx), glutathione reductase (GR) and catalase (CAT) were decreased. The present data conclude that acrylamide as neurotoxicant induces oxidative stress in developing chick embryo brain due to increasing rate of lipid peroxidation and suppress ion of the antioxidant enzymes and non-enzymatic antioxidant defense mechanism. These effects may provide an evidence for acrylamide induced neuronal damage in developing chick embryo up on the suppression and reduction of oxygen radical limiting enzymes.